Vibration Control of a High-Speed Precision Servo Numerically Controlled Punching Press: Multidomain Simulation and Experiments - Teng Xu; Qinxiang Xia; Xiaobin Long; Gianluca Buffa (Shock and Vibration)
A three-degree-of-freedom mathematical vibration model of a high-speed punching press was developed in order to explore the vibration modes of the punching press. A multidomain model of the punching press was established to predict the kinematic state during different conditions, as well as the effects of load fluctuation on the motor speed. Experimental measurements of the acceleration of the punching press were carried out. The results comparison reveals that the multidomain model is consistent with the vibration model and the experimental measurements. Modal analysis and structure modification of the punching press were conducted. The foundation at the base of the punching press was improved against excess of vibration. The effects of the dimensions of the foundation on the vibration were discussed with the aid of the multidomain model. Finally, proper foundation design, able to reduce the vibration, was obtained.